Carbon-based polymer nanocomposites for environmental and energy applications - Ismail, Ahmad Fauzi; Goh, Pei Sean (Elsevier, 2018)
Carbon-Based Polymer Nanocomposites for Environmental and Energy Applications provides the fundamental physico-chemical characterizations of recently explored carbon-based polymer nanocomposites, such as carbon nanotubes, graphene and its derivatives, nanodiamond, fullerenes and other nano-sized carbon allotropes. The book also covers the applications of carbon-based polymer nanocomposite in the environmental and energy fields. Topics range from the various approaches that have been explored and developed for the fabrication of carbon-based polymer nanocomposite, to their applications in tackling environmental and energy related issues.